En torno del asunto del yate Vita. Los recursos de la Junta de Auxilio a los Republicanos Españoles (JARE) - Velázquez Hernández, Aurelio (El Colegio de México, A.C., 2014)
This paper provides new information on the issue of the treasure carried aboard the "Vita", which unleashed huge political and historical polemics ever since the yatch arrived at Veracruz in March 1939. By recurring to sourced which had been little used and through a deep and detailed examination of the accounting books kept by the Junta de Auxilio a los Republicanos Españoles (JARE: Board for Aiding Spanish Republicans), the author managed to estimate the assets, not only carried aboard the mythical yacht, but of the whole Board.